HUBUNGAN KEPADATAN, JENIS KENDARAAN TERHADAP KADAR TIMBAL UDARA DAN URIN MASYARAKAT SEKITAR JALAN RAYA KOTA YOGYAKARTA (The Relathionship between congestion, type of vehicle with the lead air content and lead urine content of the people around the street) - T. Irwansyah; Maryadi S. Broto (Jurnal Manusia dan Lingkungan, 2003)
ABSTRAKRiset ini bertujuan untuk mencermati hubungan antara kepadatan. jenis kendaraan terhadap kadar timbal urin masyarakat yang tinggal di sekitar jalan utama di Yogyakarta. Sampel penelitian ini meliputi 40 orang yang diambil dari 4 jalan utama yaitu Malioboro, Magelang, Solo, dan KHA. Dahlan. Perhitungan jumlah dan jenis kendaraan dilakukan dengan alat pengukur jumlah kendaraan, sedangkan pengukuran kadar timbal di udara digunakan "Low Volume Air Sampler". Analisis kadar timbal di udara dan volume yang mengandung timbal digunakan "Atomic Absorbtion Spectrophotometer (AAS)", sedangkan analisis statistik digunakart regresi dan korelasi Spearment. Hasil penelitian menunjukkan bahwa terdapat hubungan yang lemah antara kepadatan kendaraan dengan kadar timbal di udara; antara kepadatan jenis kendaraan (mobil dan sepeda motor) dengan kadar timbal di udara; antara kadar timbal di udara dengan kadar timbal dalam urin orang di sekitar jalan. Kadar timbal di udara masih di bawah baku mutu lingkungan dengan rata-rata 0. 1427 ug/m3, kadar timbal dalam urin telah melampaui batas toleransi (> 0,15 mg/l). Keluhan subyektif dari masyarakat diindikasikan sebagai sakit kepala, kelelahan, nyeri otot. sakit perut dan muntah, pallor, diare dan hilangnya nafsu makan. ABSTRACTThis research was aimed to examine the relationship between congestion and types of vehicle with lead air content, lead air content with lead urine content and subjective complaints on the lead exposure of the people around the street of Yogyakarta City. The type of this research was observational using cross sectional design between congestion and types of vehicle with lead air content, lead air content with  lead urine content of the people around the street of Yogyakarta City. Sample of this research include 40m persons taken from four main streets i.e., Malioboro street, Magelang street, Solo Street and KHA Dahlan street. The computation of the number and type of vehicle was done using a measurement tool, and the measurement of lead air content was done using Low Volume Air Sampler. The analysis of lead air content and lead urine content by Atomic absorbtion spectrophotometer (AAS). Statistical analysis is use on regresson and Spearment correlation. The result of this research show more weakness relationship between vehicle congestion with lead air content (r=0,152; p=0,477); between type of vehicle (car and motorcycles) congestion with lead air content (r=0,090; p=0,677 and r=0,147; p=0,493); between lead air content with lead urine content the people around on the street (r=0,400). the lead air content was still under the standard quality with the average of 0,1427 µg/m3, the lead urine content of the people around the street average (77,5%) respondents urine sample has exceeded the tolerable limit (≤ 0,15 mg/l). Subjective complaints as a result of lead exposure that the number of were indicated as headache (59,92%0, fatigue and weakness (44,20%), muscle or senile pain (36,86%). stomachache vomiting (16,55%), pallor (10,32%), diarrhea(6,29%) and loss of appetite (2,42%).